The Effect of White Noise on Pain in Unconscious Patients with Traumatic Brain Injury - Zeynab Solimani; Naser Mozafari; Mohammad Taghi-Savadpour; Mehdi Ajri-Khameslou (Mashhad University of Medical Sciences, 2023)
Background: Most patients with traumatic brain injury (TBI) admitted to the intensive care unit experience pain. Nurses have a major role in pain management in patients with TBI.Aim: This study was performed aimed to investigate the effect of white noise on pain in unconscious patients with TBI.Method: This single-blind clinical trial study was performed in 2019 on 52 unconscious patients with TBI admitted in neurological intensive care unit in Ardabil. They were randomly assigned to the control and intervention groups. In the intervention group, patients received 30 minutes white noise for 3 consecutive days. In the control group, patients rested only on the bed at the same time. The demographic characteristics form and behavioral pain scale were used to collect data. P<0.05 was considered statistically significant.Results: The mean difference of behavioral pain score during three consecutive days 10 minutes before and 30 minutes after the intervention was 0.82 ± 0.1 in the intervention group and 0.18 ± 0.01 in the control group. Data analysis showed that the behavioral pain score in the intervention group significantly reduced compared to the control group (P <0.001).Implications for Practice: The results of this study showed that white noise could relieve the behavioral score of pain in unconscious patients with TBI. Therefore, it is recommended to use white music noise along with routine treatments to reduce the pain of unconscious patients with traumatic brain injury in the neurological intensive care unit.